1977
DOI: 10.1007/bf00380683
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogenase-nitrogenase relationship in the blue-green algaAnabaena cylindrica

Abstract: Nitrogen-fixingAnabaena cylindrica cells are found to evolve hydrogen in high quantities in the presence of CO plus C2H2. Studies with the inhibitors dichlorophenyldimethylurea (DCMU), disalicylidenepropanediamine (DSPD), dibromothymoquinone (DBMIB), undecylbenzimidazole (UDB) and chloro-carbonyl-cyanide-phenylhydrazone (CCCP) and also withAnabaena grown on nitrate- and ammonia-nitrogen show that the H2-formation is due to the ATP-dependent H3O(+)-reduction catalysed by nitrogenase. In control experiments CO p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
1

Year Published

1977
1977
1988
1988

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(45 citation statements)
references
References 33 publications
0
44
1
Order By: Relevance
“…From our findings reported earlier [3] we propose that maximum hydrogen evolution can be achieved by the suitable choice o f photosynthetic electron transport inhibitors and illumination intensity vs. a C O /acetylene gas mixture to inhibit the uptake hydrogenase [4]. Even though the former method leads to high increases over the control in air-grown cul tures highest rates in absolute values are always ob tained with material grown under nitrogen ( + C 0 2), i. e. microaerobic conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our findings reported earlier [3] we propose that maximum hydrogen evolution can be achieved by the suitable choice o f photosynthetic electron transport inhibitors and illumination intensity vs. a C O /acetylene gas mixture to inhibit the uptake hydrogenase [4]. Even though the former method leads to high increases over the control in air-grown cul tures highest rates in absolute values are always ob tained with material grown under nitrogen ( + C 0 2), i. e. microaerobic conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The latter treat ment lowers the oxygen level in the cells, thereby de creasing the activity o f the hydrogen-consuming ("uptake") hydrogenase (see also [4]). …”
Section: Introductionmentioning
confidence: 99%
“…The second reaction is the hydrogenase-dependent oxidation of H2 in some nitrogen-fixing organisms such as free living bacteria (6,15,19), blue-green algae (2), and root nodule bacteriods (7-9, 17, 18). The first reaction may decrease the energy available for the reduction of N2 (1,2,(9)(10)(11)(17)(18)(19) and for this reason has been used in the calculation of a relative efficiency value of energy utilization for N2 reduction (17,18). This value has been defined as the energy used to reduce N2 divided by the total energy consumed for nitrogenase-catalyzed substrate reduction (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…They are membrane-bound (7,12,28), couple to 02 consumption via a Cyt-containing electron transport system, and through this reaction provide a source of ATP (7, 9, 21). Several authors have suggested that these uptake hydrogenases function to recycle the H2 evolved by nitrogenase (4,7,9,21).…”
Section: Introductionmentioning
confidence: 99%
“…They are membrane-bound (7,12,28), couple to 02 consumption via a Cyt-containing electron transport system, and through this reaction provide a source of ATP (7, 9, 21). Several authors have suggested that these uptake hydrogenases function to recycle the H2 evolved by nitrogenase (4,7,9,21).In blue-green algae, membrane-bound hydrogenases can couple to two different electron transport pathways. Peschek has demonstrated respiratory H2 uptake and photosynthetic H2 uptake in Anacystis nidulans (19,20) in which the hydrogenase was induced by growth under a gas phase containing H2.…”
mentioning
confidence: 99%